The Effectiveness of Waste Management within the Framework of Green Economic Transformation and Regional Economic Performance: Empirical Evidence from the Banjarbakula Strategic Area, South Kalimantan - Patardo Haholongan Nainggolan; Laila Refiana Said; Indra Jaya Saputra; Eprinalia A (Westscience Press, 2026)
The transformation towards a green economy is a major challenge for regions still dependent on the extractive sector. Sustainable development literature emphasizes that integrating environmental policies into regional economic systems is a prerequisite for inclusive and resilient long-term growth. This study aims to analyze the influence of waste management on regional economic performance within a green economy framework in the Banjarbakula Metropolitan Area, South Kalimantan Province. The study uses a quantitative approach with an explanatory design and multiple linear regression analysis on data from 2021–2025. Waste management variables include policy and regulatory inclusiveness, budget adequacy, community participation, law enforcement effectiveness, multi-stakeholder partnerships, waste processing technology, and carbon trading, with Gross Regional Domestic Product (GRDP) as the dependent variable. The results show that waste management effectiveness through the seven independent variables mentioned above simultaneously has a significant effect on GRDP. Partially, the policy dimension, community participation, and law enforcement effectiveness show a relatively stronger influence. These findings confirm that waste management has the potential to be a strategic instrument in driving green economic transformation at the regional level.